Integrating nature-based solutions for water security in fragile mountain ecosystems: Lessons from Dhara Vikas in Sikkim, India - Ghanashyam Sharma; Yasmeen TelWala; Prakash Chettri (Nature-Based Solutions)
The Himalayan region faces escalating challenges due to climate change, particularly dwindling springs leading to water scarcity. This study examines water access, economic well-being, and ecosystem resilience in Sikkim's Himalayan region in India, using the Dhara Vikas initiative (implemented in 2008) as a case study. Fieldwork conducted from 2013 to 2015 surveyed 339 households across eight villages, representing 47.56 % of the total households reliant on approximately 63 perennial springs. The survey revealed significant economic disparities in water usage, with higher consumption among affluent groups at lower altitudes. Only 24.1 % of households had year-round water access, highlighting widespread scarcity. The initiative increased spring discharge by 30–40 %, improved water access, and diversified local economies through poultry and dairy farming. Land use and land cover (LULC) analyses from 1989, 2002, and 2013 indicated positive changes in ecosystem resilience. The study also highlights the paradoxical relationship between spring revival initiatives and increased water demand, linking this to livelihood diversification.A roadmap for spring revival is recommended, integrating nature-based solutions with Sustainable Development Goals (SDGs) and IUCN criteria to ensure effectiveness, biodiversity gains, and economic viability.Conclusions emphasize the need for rigorous data collection, collaborative partnerships, and innovative financing to bolster and expand nature-based solutions, ensuring the resilience of mountain communities amidst climate challenges. Recent extreme events, like the Teesta River flooding and glacial lake outburst floods (GLOF), underscore the urgency of such initiatives. Future research should build on this data to develop climate adaptation strategies.